Virtualized EPC: Unleashing the potential of NFV and SDN - Farhan Ahmad Khan (International Telecommunications Society (ITS), 2014)
Software Defined Networking (SDN) and Network Function Virtualization (NFV) have exploded over the telecom technology horizon in the past couple of years, surprising many with the speed at which the interest has evolved and spread. It is important to note that this is the culmination of a long effort to break up vertical proprietary stacks in telecom technology. The principles underlying both have begun to appear in some form in network standards and software over the past three to four years, priming the market for this major change. SDN is an architectural concept that encompasses the programmability of multiple network layers - including management, network services, control, forwarding and transport planes - to optimize the use of network resources, increase network agility, unleash service innovation, accelerate service time-to- market, extract business intelligence and ultimately enable dynamic, service driven virtual networks. This idea was foreshadowed in IP Multimedia Subsystem (IMS) and the architecture it inspired, in which the three layer model of data plane, control plane and applications plane set out in SDN is also present. The key idea behind IMS was modularization of network functions so that operators could buy best-of- breed product for each function. SDN effectively takes this one step further. NFV, on the other hand, aims to address various problems by leveraging standard IT virtualization technology to consolidate many network equipment types onto industry standard high volume servers, switches and storage, which could be located in Datacenters, Network Nodes and in the end user premises.
Keywords: 330